Cost performance of public infrastructure projects: the nemesis and nirvana of change-orders - Love, Peter; Irani, Z.; Smith, J.; Regan, M.; Liu, J. (Taylor & Francis, 2017)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. The cost performance of a wide range of public sector infrastructure projects completed by a contractor are analysed and discussed. Change-orders after a contract to construct an asset was signed were, on average, found to contribute to a 23.75% increase in project costs. A positive association between an increase in change orders and the contractor’s margin were identified. Taxpayers pay for this additional cost, while those charged with constructing assets are rewarded with an increase in their margins. As the public sector embraces an era of digitisation, there is a need to improve the integration of design and construction activities and engender collaboration to ensure assets can be delivered cost effectively and future-proofed. The research paper provides empirical evidence for the public sector to re-consider the processes that are used to deliver their infrastructure assets so as to reduce the propensity for cost overruns and enable future-proofing to occur.